Resistance to anthracnose and turcicum leaf blight in sorghum under dual infection. Issue 3 (29th April 2016) - Beshir, Mayada M.; Okori, Patrick; Ahmed, Nafisa E.; Rubaihayo, Patrick; Ali, Abdelbagi Mukhtar; Karim, Serunkuuma
Abstract: A half diallel mating design was used to study the inheritance of anthracnose and turcicum leaf blight (TLB) in six sorghum cultivars. Applying pathogens inoculum separately and applying both pathogens simultaneously differently affected the reaction of each genotype. GA06/18 was resistant to both pathogens. GA06/106 x Epuripuri and MUC007/009 x Epuripuri showed high heterosis for resistance to both diseases indicating that they were good materials for sorghum breeding. Additive and non‐additive (dominance) variance components were almost equally reflected by equal contribution of both variances towards the anthracnose resistance suggesting that both additive and dominance gene effects were involved in anthracnose resistance. Contribution of additive gene effects towards TLB resistance was greater than non‐additive gene effects suggesting that additive gene effects were more important in controlling TLB resistance. This study highlighted that deployment of resistant varieties is the most cost effective way to manage both diseases especially when integrated with appropriate agronomy practices.